Entraves aux théories et aux activités du mouvement pour le contrôle des naissances en France et aux États-Unis (1873-1940) - Fatma Ramdani (Itinéraires)
This article analyzes the evolution of the birth control movement after repressive laws were adopted in 1873 in the United States and in 1920 in France. The analysis of the correspondence between Margaret Sanger and the key French Neo-Malthusian leaders, Paul Robin, Eugène Humbert, and Gabriel Giroud sheds new light on the impact of such prohibiting legislation. Their letters show that, far from impeding the development of the birth control movement theories and practices, these laws increased formal and underground interactions between the militant leaders of both countries. Using the methodology of comparison and entangled history, the aim of the article is to demonstrate that such gatherings and networking proved to be strategies to bypass and infringe the repressive laws.